Effects of different insect species on seed quantity and quality in Norway spruce. (16th October 2014) - Rosenberg, Olle; Nordlander, Göran; Weslien, Jan
Abstract Grafts from selected superior trees are used for establishment of seed orchards. These seeds result in trees with higher growth rates and better wood quality than trees originating from seeds collected in local forest stands. Insecticides are used to reduce damage to seeds in seed orchards. Hypothetically, this may be ineffective because the suppression of one insect species may relieve interspecific competition and trigger corresponding increases in damage caused by another species. Therefore, we investigated the effects of three insect species [Dioryctria abietella Denis and Schiffermüller (Pyralidae), Cydia strobilella L. (Tortricidae) and Strobilomyia anthracina Czerny (Anthomyiidae)], singly and in all possible permutations, on the numbers and quality of seeds in Picea abies cones. Species were manipulated by insecticide treatments. The cones were examined for externally visible damage caused by D. abietella and S. anthracina after which the seeds were extracted, counted and X‐rayed to assess seed quality and the number of seeds infested by insects. Finally, the cones were dissected to identify and count C. strobilella larvae. There was no evidence of trade‐offs between absence of one species and increased damage by the remaining species. Instead, damage tended to increase as the number of species in a cone increased. The most serious pest species in the present study was D. abietella, reducing the number of filled seeds by approximately 60%. Our results indicate that there is little risk that suppression measures directed towards one particular species will lead to increased damage by other species. The insecticide, α‐cypermethrin, showed promising results against D. abietella and S. anthracina.